2013
DOI: 10.1111/jfd.12169
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal response of rainbow trout to Ichthyobodo necator: immunohistochemical and gene expression studies indicate a Th1‐/Th2‐like switch

Abstract: Infections with the parasitic flagellate Ichthyobodo necator (Henneguy, 1883) cause severe skin and gill disease in rainbow trout Oncorhynchus mykiss (Walbaum, 1792) juveniles. The epidermal disturbances including hyperplasia and mucous cell exhaustion caused by parasitization are known, but no details on specific cellular and humoral reactions have been presented. By applying gene expression methods and immunohistochemical techniques, further details of immune processes in the affected skin can be presented. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 43 publications
4
28
0
Order By: Relevance
“…In kidney, il ‐ 1β expression was up‐regulated during virus infections while in skin, expression was up‐regulated during sea lice infections. These results agree with previous single infection studies, and therefore, we can conclude that expression of il ‐ 1β does not appear to be negatively impacted by co‐infection in sockeye salmon (Braden et al, ; Chettri et al, ; Purcell et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…In kidney, il ‐ 1β expression was up‐regulated during virus infections while in skin, expression was up‐regulated during sea lice infections. These results agree with previous single infection studies, and therefore, we can conclude that expression of il ‐ 1β does not appear to be negatively impacted by co‐infection in sockeye salmon (Braden et al, ; Chettri et al, ; Purcell et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…Most recently, in a comparative study of Braden et al (2015), high induction of cathelicidin was observed in lice-challenged sockeye and Atlantic salmon compared to the more resistant coho, suggesting the existence of species-specific mechanisms of resistance. Up-regulation of cathelicidin was previously also reported in rainbow trout in response to ectoparasitic Ichthyophthirius multifiliis (Heinecke and Buchmann, 2013), and Ichthyobodo necator (Chettri et al, 2013). A large part of findings are in favour of limited accessibility of nutrients as a major factor that could hinder successful establishment of lice on the host.…”
Section: E-bc T-bc C-3 E-3 T-3 C-16 E-16 T-16mentioning
confidence: 68%
“…In addition, salmon louse Lepeophtheirus salmonis infections of Atlantic salmon skin was associated with an upregulation of the arginase gene (59). A related switch from a Th1 to a Th2-like reaction in rainbow trout skin infected with flagellates was recently described (60). So although M1 and M2 differentiation has not yet been detected in invertebrates, at least fish seems to have developed arginase, which makes M1 and M2 differentiation possible.…”
Section: Evolution Of Macrophage Functionmentioning
confidence: 84%